Steadfast heart - Peterson, Tracie (Minneapolis, Minnesota Bethany House, a division of Baker Publishing Group, 2015)
"In 1880s Seattle, Washington, Lenore Fulcher desires love while so many around her are finding it; when lawyer Kolbein Booth arrives searching for his sister at a finishing school for mail-order brides, he and Lenore face danger and uncertainty amidst their growing attraction"--
1
Keywords: First loves -- Fiction; Man-woman relationships -- Fiction; Seattle (Wash.) -- Social life and customs -- 19th century -- Fiction; Historical fiction; Love stories